Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2015)
Highly stable Cu(0) nanoparticles were synthesized on reduced graphene oxide (rGO) sheets using a cost-effective and green method. The synthesized Cu(0)-nanoparticle-rGO composites exhibit excellent catalytic activity for the synthesis of symmetrical biaryls from arylboronic acids under microwave irradiation. The reaction proceeds smoothly in base-free conditions with easy recovery and reuse of the catalyst. The methodology is compatible with various functional groups and provides an attractive protocol for the synthesis of symmetrical biaryls with very good yields. HRTEM, XPS and XRD analyses showed the catalyst to be recyclable. The Cu(0) nanoparticles are stable in the rGO nanosheets, and the particle size distribution and oxidation state of the Cu(0) nanoparticle remain the same after performing the chemical reaction.